Vegetal-Derived Bioactive Compounds as Multidrug Resistance Modulators in Colorectal Cancer - Francisco Quiñonero; Cristina Mesas; Mercedes Peña; Laura Cabeza; Gloria Perazzoli; Consolación Melguizo; Raul Ortiz; Jose Prados (Applied Sciences, 2023)
Colorectal cancer is one of the leading causes of morbidity and mortality today. Knowledge of its pathogenesis has made it possible to advance the development of different therapeutic strategies. However, the appearance of drug resistance constitutes one of the main causes of treatment failure. Bioactive compounds of vegetable origin are being studied as a new strategy to improve antitumor treatment, due to their ability to regulate the pathways involved in the development of carcinogenesis or processes that are decisive in its evolution, including multidrug resistance. In vitro and in vivo studies of these substances in combination with cytotoxic drugs have shown that they reduce resistance and increase therapeutic efficacy. The objective of this review is to summarize the knowledge that is described in the scientific literature on the antitumor and chemo-sensitizing capacity of vegetable-derived biomolecules such as polyphenols, flavonoids, and terpenes. These compounds may hold a promising future in improving the treatment of colorectal cancer.